Colonialism, plantation and Anthropocene: the control over bodies and territories - Wedig, Josiane Carine; Ramos, João Daniel Dorneles (Revista do Instituto de Estudos Brasileiros, 2023)
In this essay, we present an analysis of the transformations caused in Holocene agriculture by plantation. Since colonialism, processes were instituted that produced devastating changes on the planet, destroying space-times of refuges for people and other beings, which caused the Anthropocene – a period that refers to geological mutations resulting from human action. As opposed to this extractive model of bodies and territories, we will discuss agroecology as a correlation of practices, social movements and sciences, that connect modes of existence and ancestral knowledge of the peoples of the earth, creating possibilities for multispecies resurgence in the face of catastrophes.